1987
DOI: 10.1902/jop.1987.58.7.451
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Delivery Methods of Chlorhexidine in Handicapped Children: I. Effects on Plaque, Gingivitis, and Toothstaining

Abstract: In handicapped groups, the maintenance of oral hygiene can be a major problem, and chemical plaque control offers many advantages. This study compared the effectiveness of chlorhexidine gluconate, delivered as a 0.2% mouthrinse, a 0.2% spray, and a 1% gel in trays, in controlling dental plaque and gingival bleeding in a group of 49 spastic children. All three delivery methods produced an improvement in plaque and gingival bleeding scores. However, the gel was significantly more effective than either the mouthw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
85
2
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 22 publications
(2 reference statements)
1
85
2
1
Order By: Relevance
“…8 Another study with handicapped children further confirmed that CHG gel was significantly more effective than either the mouthwash or spray in controlling dental plaque. 9 Therefore, in line with our finding, oral hygiene care using CHG gel seems to be more effective at reducing VAP than CHG mouthwash.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…8 Another study with handicapped children further confirmed that CHG gel was significantly more effective than either the mouthwash or spray in controlling dental plaque. 9 Therefore, in line with our finding, oral hygiene care using CHG gel seems to be more effective at reducing VAP than CHG mouthwash.…”
supporting
confidence: 83%
“…This finding may be explained by the effectiveness of CHG gel for performing oral hygiene in previous studies. 8,9 A double-blind placebocontrolled multicenter study in ICUs showed that antiseptic decontamination of gingival and dental plaque with a CHG gel significantly decreased the oropharyngeal colonization by aerobic pathogens in ventilated patients. 8 Another study with handicapped children further confirmed that CHG gel was significantly more effective than either the mouthwash or spray in controlling dental plaque.…”
mentioning
confidence: 99%
“…Although 15 mL is the CHX recommended dose for an oral rinse in alert patients, our pilot data 15 and others 16 show that as little as 2 mL is adequate to cover the oral cavity using a researcherapplied swabbing technique. In addition, aspiration of the solution in this obtunded population is a risk.…”
Section: Chx Intervention and Usual Carementioning
confidence: 64%
“…The recommended mouthwashes are those with proven scientific evidence of efficacy, safety, and significant effect in both the short and the long term against biofilm, gingivitis and, ideally, against caries, and should also demonstrate efficacy against a wide variety of Gram+ and Gram-bacterial species. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] Several studies have demonstrated that most patients do not clean biofilm effectively in interdental areas, or even maintain optimal long-term oral hygiene levels, and have observed a gingivitis prevalence ranging from 85% to 90% in the Latin American population, in disabled individuals or even those having no special impairment. 26 This situation is aggravated in elderly adults, where dental biofilm retention is a problem because of the existence of defective restorations, exposed root surfaces, or others reasons.…”
mentioning
confidence: 99%
“…Some authors suggest that mouthwashes may be an effective response to the oral hygiene problem in disabled individuals. 36 Ideally, an effective antiseptic must penetrate the biofilm. 37 Recent studies have suggested that bacterial phenotypes may change when the microorganisms turn from a planktonic condition (in suspension or freely floating) to a sessile condition (as part of a biofilm).…”
mentioning
confidence: 99%